2005
DOI: 10.1128/jvi.79.20.12893-12904.2005
|View full text |Cite
|
Sign up to set email alerts
|

Virus Infection Switches TLR-3-Positive Human Neurons To Become Strong Producers of Beta Interferon

Abstract: To study the capacity of human neurons to mount innate immunity responses to viral infections, we infected cells of a human postmitotic neuron-derivative cell line, NT2-N, with rabies virus (RABV) and herpes simplex type 1 (HSV-1). Changes in neuronal gene expression were analyzed by use of Affymetrix microarrays. Applying a twofold cutoff, RABV increased the transcription of 228 genes, and HSV-1 increased the transcription of 263 genes. The most striking difference between the two infections concerns genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
270
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(294 citation statements)
references
References 77 publications
20
270
2
2
Order By: Relevance
“…These receptors have been shown to initiate antiviral programs and activate innate immune responses in the CNS (35,44). Recently, human neuron-like NT2 cells were shown to also express TLR3 and to respond to poly(I:C) stimulation by producing IFN-␤ (38). Interestingly, we found that protection against CMV infection after poly(I:C) treatment was greater than that conferred by treatment with IFN-␣ in human astrocytes and primary brain cultures, indicating the efficiency of this signaling pathway in inducing an antiviral response in cells of the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors have been shown to initiate antiviral programs and activate innate immune responses in the CNS (35,44). Recently, human neuron-like NT2 cells were shown to also express TLR3 and to respond to poly(I:C) stimulation by producing IFN-␤ (38). Interestingly, we found that protection against CMV infection after poly(I:C) treatment was greater than that conferred by treatment with IFN-␣ in human astrocytes and primary brain cultures, indicating the efficiency of this signaling pathway in inducing an antiviral response in cells of the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia [16] Astrocytes [10,110] Neurons [112] Astrocytes [111] Microglia [15] Neurons [12] Astrocytes [58] Neurons [112] Neurons [12] TLR4 Microglia [16] Astrocytes [16,110] Microglia [15] Astrocytes [11,111] Neurons [12] Astrocytes [58] Neurons [12,13] …”
Section: Tlr3mentioning
confidence: 99%
“…Induction of Type 1 IFN gene expression is an essential component of innate immunity (22,23). Recent studies (24) have also shown that neurons produce high levels of IFN-␤ through TLR 3 signaling.…”
mentioning
confidence: 99%